PENGEMBANGAN EKONOMI ISLAM BERBASIS KEPENDUDUKAN DI PERDESAAN - Kusmanto, Thohir Yuli (Da'wa and Communication Faculty State Islamic University Walisongo, Semarang, Indonesia, 2014)
Nowadays, Islamic economy is growing and developing considerably in Indonesia. It is considered as a better alternative of the earlier economic systems which are traditional (communal) and capitalist economy. These two economic systems did not quite give way to get a prosperous life for Indonesian people. The existing Islamic economics hopefully might answer this problem. So, organizing Islamic economic system as a discourse and praxis must be developed in the community’s life. The growth and development of Islamic economic institutions were initially an urban phenomenon. However, lately it has been gone through rural areas. The efforts to develop the role and contribution of Islamic economic institutions in rural areas, can take advantage of the conditions of rural population. Understanding the composition of the population might help to establish economic institutions, to distribute funds and to develop various forms of business.***Ekonomi Islam tumbuh dan berkembang di Indonesia, sebagai alternatif dari sistem ekonomi yang terlebih dahulu ada yaitu ekonomi tradisional (komunal) dan kapitalis. Kedua sistem ekonomi yang ada tidak cukup mampu memberikan jalan menuju kehidupan sejahtera bagi masyarakat Indonesia. Hadirnya ekonomi Islam, tentu harus mampu menjawab persoalan tersebut. Pelembagaan dan pengorganisasian sistem ekonomi Islam baik sebagai wacana dan praksis harus berlangsung dalam kehidupan masyarakat. Pertumbuhan dan perkembangan lembaga ekonomi Islam, pada awalnya merupakan fenomena perkotaan. Namun akhir-akhir ini telah merambah pedesaan. Upaya pengembangan peran dan kontribusi lembaga ekonomi Islam di perdesaan, bisa memanfaatkan kondisi kependudukan di perdesaan. Pemahaman komposisi penduduk akan membantu dalam mendirikan lembaga ekonomi, mendistribusikan dana dan mengembangkan berbagai bentuk usaha.